Surface Crack Detection in Prestressed Concrete Cylinder Pipes Using BOTDA Strain Sensors. (21st August 2017) - Xu, Zhigang; Feng, Xin; Zhong, Sheng; Wu, Wenjing
Abstract : Structural deterioration after a period of service can induce the failure of prestressed concrete cylinder pipes (PCCPs), with microcracks in the coating leading to the corrosion of the prestressed wires. In this paper, we propose the use of Brillouin optical time-domain analysis (BOTDA) strain sensors for detecting the onset of microcracking in PCCP coating: the BOTDA strain sensors are mounted on the surface of the PCCP, and distributed strain measurements are employed to assess the cracks in the mortar coating and the structural state of the pipe. To validate the feasibility of the proposed approach, experimental investigations were conducted on a prototype PCCP segment, wherein the inner pressure was gradually increased to 1.6 MPa. Two types of BOTDA strain sensors—the steel wire packaged fiber optic sensor and the polyelastic packaged fiber optic sensor—were employed in the experiments. The experimental distributed measurements agreed well with the finite element computations, evidencing that the investigated strain sensors are sensitive to localized deterioration behaviors such as PCCP microcracking.